2006
DOI: 10.1002/esp.1326
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rock uplift and rock resistance on river morphology in a subduction zone forearc, Oregon, USA

Abstract: Relationships between riverbed morphology, concavity, rock type and rock uplift rate are examined to independently unravel the contribution of along-strike variations in lithology and rates of vertical deformation to the topographic relief of the Oregon coastal mountains. Lithologic control on river profile form is reflected by convexities and knickpoints in a number of longitudinal profiles and by general trends of concavity as a function of lithology. Volcanic and sedimentary rocks are the principal rock typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 78 publications
1
29
0
Order By: Relevance
“…Other examples of lithology influencing channel concavity (and steepness) are documented for streams draining the Santa Ynez Mountains, California (Duvall et al 2004), and the Oregon coastal mountains ( VanLaningham et al 2006), andMiller (1958) demonstrates an important role for lithology in channel slope and morphology in the Sangre de Cristo Range, New Mexico. On the other hand, Brookfield (1998) argues for absence of lithological control of regional-scale river slopes fringing the Himalayas in favor of discontinuities being the product of differential rock uplift or river capture.…”
Section: Substrate Erodibility Effects and Scale Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…Other examples of lithology influencing channel concavity (and steepness) are documented for streams draining the Santa Ynez Mountains, California (Duvall et al 2004), and the Oregon coastal mountains ( VanLaningham et al 2006), andMiller (1958) demonstrates an important role for lithology in channel slope and morphology in the Sangre de Cristo Range, New Mexico. On the other hand, Brookfield (1998) argues for absence of lithological control of regional-scale river slopes fringing the Himalayas in favor of discontinuities being the product of differential rock uplift or river capture.…”
Section: Substrate Erodibility Effects and Scale Dependencementioning
confidence: 99%
“…Measures of concavity (C i and v) vary widely in the study catchments and are not systematically scaled with drainage area or substrate erodibility. If concavity is influenced by lithological controls, as suggested by VanLaningham et al (2006) for the Oregon coastal mountains, such effects are restricted to the subcatchment scale in western Scotland.…”
Section: Catchment-scale Effects Of Lithological Controlsmentioning
confidence: 99%
“…The morphology of longitudinal profiles are the consequence of complex interactions between a range of variables (e.g., lithological contrasts, structural features, tectonic episodes, climate, landslides, stream power, and anthropogenic interferences) (Seeber and Gornitz, 1983;Merritts and Vincent, 1989;Moglen and Bras, 1995;Sklar and Dietrich, 1998;Hurtrez et al, 1999;Stock and Montgomery, 1999;Whipple and Tucker, 1999;Snyder et al, 2000;Kirby and Whipple, 2001;Duvall et al, 2004;Whipple, 2004;VanLaningham et al, 2005;Korup, 2006;Ouimet et al, 2007). In the present study, we used the longitudinal river profile and SL to identify morphotectonic anomalies and their correlation with controlling factors, i.e., lithology and tectonics; however, other factors affecting the stream gradient are not addressed in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Our results agree with Duvall et al [7] who indicated streams flowing from resistant to less resistant bedrock exhibit highly concave profiles and increased gradients along their lower reaches. In addition, VanLaningham et al [43] noted that rivers on more resistant rocks have lower longitudinal concavity.…”
Section: Sl and Hack Profilesmentioning
confidence: 99%